Quercetin as a therapeutic agent for acute pancreatitis: a comprehensive review of antioxidant, anti-inflammatory, and immunomodulatory mechanisms - Jiang, Zeyi; Lhamo, Gamar; Ma, Mengjie; Ye, Xuxia; Chen, Jin; He, Yibo; Xu, Jian; Huang, Liquan (Frontiers in Pharmacology, 2025)
Acute pancreatitis (AP) is a severe inflammatory disorder of the pancreas, characterized by high morbidity and mortality rates. Despite significant advancements in understanding the pathophysiological mechanisms of AP, current treatment options still face considerable limitations. Recent studies have underscored the therapeutic potential of quercetin, a natural flavonoid, due to its potent antioxidant, anti-inflammatory, and immunomodulatory properties, positioning it as a promising therapeutic candidate for AP. This review explores the effects of quercetin on AP, highlighting its antioxidant activities, its role in immune modulation, and its protective effects on pancreatic tissue. Furthermore, it examines quercetin’s multi-target mechanisms and its advantages over conventional therapies, such as N-acetylcysteine and corticosteroids. Although preliminary studies suggest that quercetin can alleviate inflammation and oxidative stress in AP, clinical evidence remains limited. One of the main challenges for quercetin’s clinical application is its low bioavailability. Future research should focus on strategies to enhance its bioavailability and on conducting large-scale randomized controlled trials to more comprehensively assess its efficacy and safety in the treatment of AP.